A High‐Performing Direct Carbon Fuel Cell with a 3D Architectured Anode Operated Below 600 °C. Issue 4 (8th December 2017) - Wu, Wei; Zhang, Yunya; Ding, Dong; He, Ting
Abstract: Direct carbon fuel cells (DCFCs) are highly efficient power generators fueled by abundant and cheap solid carbons. However, the limited triple‐phase boundaries (TPBs) in the fuel electrode, due to the lack of direct contact among carbon, electrode, and electrolyte, inhibit the performance and result in poor fuel utilization. To address the challenges of low carbon oxidation activity and low carbon utilization, a highly efficient, 3D solid‐state architected anode is developed to enhance the performance of DCFCs below 600 °C. The cell with the 3D textile anode framework, Gd:CeO2 –Li/Na2 CO3 composite electrolyte, and Sm0.5 Sr0.5 CoO3 cathode demonstrates excellent performance with maximum power densities of 143, 196, and 325 mW cm −2 at 500, 550, and 600 °C, respectively. At 500 °C, the cells can be operated steadily with a rated power density of ≈0.13 W cm −2 at a constant current density of 0.15 A cm −2 with a carbon utilization over 85.5%. These results, for the first time, demonstrate the feasibility of directly electrochemical oxidation of solid carbon at 500–600 °C, representing a promising strategy in developing high‐performing fuel cells and other electrochemical systems via the integration of 3D architected electrodes. Abstract : A 3D architectured framework is fabricated and applied as anode for high‐performing direct carbon fuel cells. The fuel cells demonstrate remarkable power densities below 600 °C, attributed to highly improved mass transfer and increased triple‐phase boundaries within the 3D anode. This approach provides a promising strategy in developing 3D functional electrodes for fuel cells and other electrochemical devices.